The regulatory role of mine soil properties in the growth of revegetation plants in the post-mine landscape of East Kalimantan. (June 2022) - Iskandar, Iskandar; Suryaningtyas, Dyah Tjahyandari; Baskoro, Dwi Putro Tejo; Budi, Sri Wilarso; Gozali, Imam; Saridi, Saridi; Masyhuri, Muhammad; Dultz, Stefan
Graphical abstract: Highlights: Evaluation of quality of mine soils and revegetation plants in East Kalimantan. Similar impact of soil physical properties on productivity of mine soils determined. Soil chemistry has a regulatory role on the growth of revegetation plants. Soil quality evaluations indicate the most vulnerable post-coal mine landscapes. Need of soil amendments to establish fast revegetation of acid mine soils. Abstract: The growth of revegetation plants in post-mining areas is determined by the mine soil quality, which strongly depends on the physical and chemical properties of the original soil. Visual observation of revegetation plants in two ex-coal mining areas in East Kalimantan, i.e. Lati and Sambarata sites, showed a clear difference in plants growth. This research aims to study the role of the physical and chemical properties of mine soil on the growth rate of revegetation plants so that it can be used to develop a sustainable ex-mining land reclamation strategy. The observation plots on each ex-mining land were grouped into (0–2), (2–4), (4–6), (6–8), (8–10), and (10–12) years since revegetation. In each group, soil sampling was carried out at a depth of 0–30 cm for analysis of soil physical and chemical properties. Observations were also made on the development of plant growth. The better revegetation plant growth at Sambarata site compared to those at Lati site was indicated by the composition of the stand structure, stem diameter, and plant height. Both sites have a similar texture, which is dominated by silt, and slightly higher bulk densities at Sambarata site compared to those at Lati site. Hence, not soil physical properties but soil chemistry played a regulatory role in the growth of revegetation plants. Here, the exchangeable cations at Sambarata site were dominated by Ca 2+ and Mg 2+, whereas those at Lati site were dominated by Al 3+ . Linked with a high base saturation, the pH, organic C, total N, and available P2 O5 mine soil quality of the Sambarata site were more favourable for plants growth. Thus, in reclamation activities in post-mining areas, soil quality improvement using lime, rock phosphate, and compost is indispensable to increase soil fertility and establish fast revegetation.